Integrating Science and Religion through Ontological and Historical Approaches in Islamic Education: Integrasi Sains dan Agama melalui Pendekatan Ontologis dan Historis dalam Pendidikan Islam - Sefhia Qurrotu Ainina (Averroes: Journal for Science and Religious Studies, 2024)
This study focuses on the role of ontological and historical approaches in harmonizing science and religion as a paradigm for integrative knowledge development in Islamic higher education. The research problem centers on how concepts of ontology and history can construct a holistic educational framework that integrates science and religion, as well as the challenges encountered in achieving this integration. The study employs a qualitative approach, utilizing document analysis and literature review methods, encompassing various scholarly sources related to ontological concepts, the historical development of knowledge, and integration models in Islamic education. The main findings reveal that the ontological and historical approaches can enrich integrative knowledge by providing a robust philosophical foundation for uniting scientific and religious values within Islamic educational frameworks. The study’s contribution lies in developing a more profound concept of integration, which not only unites science and religion at a practical level but also offers a philosophical foundation for their interaction within the curriculum. The conclusion emphasizes that the ontological and historical approaches are essential for creating a holistic Islamic educational paradigm, though further empirical research is needed to assess its effectiveness in educational settings to strengthen the implementation of integrative knowledge.